Transfuges de classe – La fin d’un récit ? - Lionel Ruffel (Contextes, 2025)
The intense focus on narratives of class defectors does not necessarily reflect the manuscripts received by publishing houses or those worked on in creative writing programs. Based on his dual professional experience, Lionel Ruffel concludes that aspiring authors offer very few narratives of class defectors, despite an increasing number of personal writings. Moreover, it appears that some of these authors criticize the narrative of social mobility promoted by class defector stories, favoring a more intersectional approach. Finally, Lionel Ruffel interprets the increase in personal writings as a consequence of the book market’s disruption, which sees ever more new releases published, while the readership does not increase proportionately. Thus, visibility strategies through personalization are seen as the most effective.